Sorption of Ni(II) and Cr(III) ions by the Chironomus yoshimatsui larvae from wastewater - Ryoo, Keon Sang (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
In this study, Chironomus yoshimatsui larvae were applied to remove Ni(II) and Cr(III) ions from wastewater. The sorption studies were carried out using laboratory-reared C. y. larvae. It was found that C. y. larvae are very susceptible to Cr(III) as compared to Ni(II). The survival capacity of C. y. larvae was sharply reduced when exposed to even low Cr(III) concentration. Sorption isotherm and kinetics of C. y. larvae for Ni(II) were determined by means of controlled experiments in a batch system. It was observed that sorpyion efficiency of Ni(II) was largely concentration dependent and more effective at lower concentration. At each equilibrium, Ni(II) was removed up to roughly 44âˆ¼80 %. Sorption data were better fitted to the Langmuir isotherm model because of its correlation coefficient R2 value greater than that of the Freundlich isotherm model. The sorption kinetics by C. y. larvae for Ni(II) was well described a pseudo-first-order rate expression. C. y. larvae have enormous potential for application in wastewater treatment technologies because they are widespread and abundant all around the world and can be easily kept in culture.